2020
DOI: 10.3390/en13205238
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced CH4-CO2 Hydrate Swapping in the Presence of Low Dosage Methanol

Abstract: CO2-rich gas injection into natural gas hydrate reservoirs is proposed as a carbon-neutral, novel technique to store CO2 while simultaneously producing CH4 gas from methane hydrate deposits without disturbing geological settings. This method is limited by the mass transport barrier created by hydrate film formation at the liquid–gas interface. The very low gas diffusivity through hydrate film formed at this interface causes low CO2 availability at the gas–hydrate interface, thus lowering the recovery and repla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 90 publications
(126 reference statements)
1
35
0
Order By: Relevance
“…Industrial-scale adaptation of CO 2 capture from CO 2 -N 2 mixture requires a minimum of three stages to separate and capture 98-99 mol% [47]; however, CO 2 sequestration into geological formations would involve a single step, hence higher CO 2 recovery as hydrate is an essential requirement. In our previous study, we had demonstrated that when CO 2 was injected into methane hydrate reservoir in the presence of SDS or L-methionine, CO 2 recovery was found to be in the range of 88-89% without any methane recovery [13]. A potential application of L-methionine during CO 2 hydrate capture and storage is also demonstrated in another study [99].…”
Section: Co 2 Split Fraction Analysismentioning
confidence: 84%
See 3 more Smart Citations
“…Industrial-scale adaptation of CO 2 capture from CO 2 -N 2 mixture requires a minimum of three stages to separate and capture 98-99 mol% [47]; however, CO 2 sequestration into geological formations would involve a single step, hence higher CO 2 recovery as hydrate is an essential requirement. In our previous study, we had demonstrated that when CO 2 was injected into methane hydrate reservoir in the presence of SDS or L-methionine, CO 2 recovery was found to be in the range of 88-89% without any methane recovery [13]. A potential application of L-methionine during CO 2 hydrate capture and storage is also demonstrated in another study [99].…”
Section: Co 2 Split Fraction Analysismentioning
confidence: 84%
“…Depleted methane hydrate reservoirs are also proposed as the potential CO 2 storage site for injecting CO 2 or CO 2 /N 2 mixtures [11,12]. In our recent experimental study [13], no CH 4 production was observed after CO 2 injection into methane hydrate-bearing sediments when a hydrate promoter (HP), such as sodium dodecyl sulfate (SDS) or L-methionine, was present in water. This was caused due to quick CO 2 hydrate layer formation as well as methane hydrate reformation in the presence of HPs.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…For example, it can improve the replacement efficiency by injecting the additive (methanol) in the CH 4 −CO 2 replacement processes, which have high electrostatic interaction with H 2 O molecules. 46 4. At 0 ns, the initial configurations reveal the two-layer system composed of a gas layer (on the right) and a hydrate layer (on the left).…”
Section: Resultsmentioning
confidence: 99%